Role and Responsibility of Guardian in Manage of Inheritances Under Supervision of Medan Inheritances Center, Indonesia - Tamba, Roida; Habeahan, Besty (Golden Ratio of Data in Summary, 2025)
The role of the facilitator is vital in managing assets for the underprivileged, including minors or individuals who are legally considered incompetent. The facilitator is responsible for ensuring that the management of assets is carried out by regulations and protecting the interests of the heirs he represents. Supporting actions, especially those related to asset management or sale, require BHP approval to prevent misuse. This study uses a normative legal research method that examines legal principles and systematics through an approach to legislation and literature search. The study results show that the sponsor and BHP have a crucial role in ensuring fair management of heritage assets by the provisions of the law. The Heritage Center functions as a supervisor who ensures that the custodian carries out his duties in good faith and that every action of the custodian is carried out to protect the interests of the heirs. With the existence of BHP, the rights of heirs under custody can be protected to the maximum, and the potential for misuse of heritage assets can be prevented.